Loss of Fatty Acid Binding Protein 4/aP2 Reduces Macrophage Inflammation Through Activation of SIRT3 - Xu, Hongliang (Mol Endocrinol, 2016)
Activation of proinflammatory macrophages plays an important role in the pathogenesis of insulin resistance, type 2 diabetes, and atherosclerosis. Previous work using high fat-fed mice has shown that ablation of the adipocyte fatty acid binding protein (FABP4/aP2) in macrophages leads to an antiinflammatory state both in situ and in vivo, and the mechanism is linked, in part, to increased intracellular monounsaturated fatty acids and the up-regulation of uncoupling protein 2. Here, we show that loss of FABP4/aP2 in macrophages additionally induces sirtuin 3 (SIRT3) expression and that monounsaturated fatty acids (C16:1, C18:1) lead to increased SIRT3 protein expression. Increased expression of SirT3 in FABP4/aP2 null macrophages occurs at the protein level with no change in SirT3 mRNA. When compared with controls, silencing of SIRT3 in Raw246.7 macrophages leads to increased expression of inflammatory cytokines, inducible nitric oxide synthase and cyclooxygenase 2. In contrast, loss of SIRT3 in FABP4/aP2-deficient macrophages attenuates the suppressed inflammatory signaling, reduced reactive oxygen species production, lipopolysaccharide-induced mitochondrial dysfunction, and increased fatty acid oxidation. These results suggest that the antiinflammatory phenotype of FABP4/aP2 null mice is mediated by increased intracellular monounsaturated fatty acids leading to the increased expression of both uncoupling protein 2 and SirT3.